Age peculiarity manifestation of antioxidant effect of 6-hexyl-3,6-dimethyl-6,7-dihydro-2H-[1,2,4]triazino[2,3-c]quinazolin-2-one on rats under the intermittent hypobaric hypoxia - Shvets, V. M.; Voskoboynik, A. Yu.; Berest, G. G.; Kovalenko, S. I.; Agibailov, M. V.; Kulchitskiy, O. K.; Kulchitska, N. O.; Davydov, V. V.; Швець, Володимир Миколайович; Воскобойнік, Олексій Юрійович; Берест, Галина Григорівна; Коваленко, Сергій Іванович; et al. (My University, 2019)
The organism of an old human as well as an experimental animal has decreased adaptive abilities and increased sensitivity to the effect of adverse environmental factors. We point out the high relevance of the search of new pharmacological compounds that have strong antioxidant properties and can be used to treatment and prevention of cardiovascular diseases with ageing. Aims and Objective: The aim of the study was to investigate the antioxidant activity of 6-hexyl-3,6-dimethyl-6,7-dihydro2H-[1,2,4]triazino[2,3-c]quinazolin-2-one (HTQ). Materials and Methods: Two groups of nonlinear male Wistar rats: 6–8 months (adult) and 24–26 months (old) were used. Determination of the myocardial diene conjugates and products reacting with 2-thiobarbituric acid (TBA-AP) concentration was carried out. Results: Concentrations of diene conjugates in adult and old rats, which were administered HTQ, were 21% and 32%, respectively, lower compared to animals to which the synthesized compound was not administered. After administration of HTQ, the concentration of TBA-AP in old animals decreased by 23% as compared with the animals of the control group. Conclusion: An administration of HTQ has limited the accumulation of intermediate lipid peroxidation products in the hearts of old animals in the condition of hypoxia.
Keywords: Aging; hypoxia; lipid peroxidation; myocardium